India’s Vaccine Diplomacy and Global Health Governance: A Soft Power Approach in the Context of Public Policy and Religious Values - Mondal, Joyprokash (FISIP UIN Sunan Gunung Djati Bandung, 2024)
Research Problem: India's vaccine diplomacy during the Covid-19 pandemic has not only emerged as a significant tool of soft power but also involves moral and ethical dimensions closely tied to religious values and public policy. In the midst of a global crisis, the interaction between India’s vaccine diplomacy and the religious and public policy frameworks of recipient nations requires deeper exploration. Research purposes: This article aims to analyze the role of India’s vaccine diplomacy in relation to public policy and religious values in recipient countries, examining how India’s global health initiatives influence moral and ethical perceptions of vaccine distribution, fairness, and international solidarity. Research methods: The study employs policy analysis through a comprehensive literature review, focusing on the relationship between vaccine diplomacy, public policy, and responses from religious communities in the recipient countries. It also explores the ethical and spiritual dimensions of India’s health diplomacy approach and its impact on public health policies. Results and Discussion: The findings reveal that India’s vaccine diplomacy, through initiatives like